Realizing high-performance four active plasmonic filters using a single structure - Samar Elbialy; B. M. El-den; Eman Ashraf (Scientific Reports)
Abstract This research aims to contribute significantly to the field of plasmonic filtering technology within modern optical communication systems. By focusing on the development of a high-performance, more compact, and efficient design, this study explores the potential of hybrid plasmonic filters to revolutionize optical filtering applications. The approach leverages an innovative active material with electrically tunable permittivity, allowing for dynamic control over the filter’s optical properties. The research specifically examines four types of filters: low-pass filters (LPF), high-pass filters (HPF), band-pass filters (BPF), and band-reject filters (BRF). These filters are designed to operate effectively across a broad wavelength range of 1200–1800 nm, achieving a transmittance exceeding 98% at the output port, while maintaining isolation with transmittance below 2% at the isolated ports. The structure demonstrates a FWHM of approximately 216 nm for the band-pass filter and approximately 223 nm for the band-reject filter, which are considered moderate values, ensuring the versatility and multifunctionality of the design. The ultra-compact size, with a footprint of just 21 µm2, makes these filters particularly advantageous for integration into space-constrained optical communication systems.